Respuesta :

Answer: [tex]x= \frac{-1+\sqrt{97} }{8} , \frac{-1-\sqrt{97} }{8}[/tex]

Step-by-step explanation:

Use the Quadratic Formula .. if you use Completing the Square it'll take longer!!

In general, given [tex]ax^{2} +bx+c=0[/tex] , there exists two solutions where:

[tex]x=\frac{-b+\sqrt{b^{2} -4ac} }{2a}[/tex] , [tex]\frac{-b-\sqrt{b^{2} }-4ac}{2a}[/tex]

In this case, a=4 , b=1 and c= -6

[tex]x= \frac{-1+\sqrt{1-4*4*-6} }{2*4}[/tex] , [tex]\frac{-1-\sqrt{1-4*4*-6} }{2*4}[/tex]

Simplify.

[tex]x=\frac{-1+\sqrt{97} }{8}[/tex] , [tex]\frac{-1-\sqrt{97} }{8}[/tex]